Law at work 2019. The trade union guide to employment law (London, 2019)
"The 2019 edition of Law at Work has been completely revised and updated to include all new and current employment legislation and the most up-to-date case law examples. Law at Work 2019 clearly explains the key areas of employment law, enabling reps and individuals to identify their legal rights. Unlike most other publications on employment law, it examines the law from the perspective of trade unions and workers."